Peculiarities of Past Tense Grammatical Expression in Short Prosaic Forms of the Serbian Literary Discourse of the 20th–21st centuries - Yarmak , Veronika (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article deals with semantic and emotional load of Serbian verb's analytical and synthetic forms as explicit means of past tense expression in stylized epistolary fragments of short prose forms of Serbian classical literary discourse of different epochs. The author consistently considers stylized epistolary passages from tales by eminent Serbian writers: L. Lazarević, Y. Vselinović, І. Sekulić, М. Кapora, noting the key role of perfects, aorists, imperfects, pluperfects in chronotopes of short stories with a relatively clear configuration (when a retrospection of linear event sequence is present) and rather vague boundaries (in cases when letters are peculiar to time dialogue between writer and reader). Particular attention is paid to investigation of functions of preterit verb forms in stylized letters drawn towards reporting people about actual events. The author's attention is also focused on the mechanisms of creating the so-called intimization effect and the role of various Serbian past tense verb forms in this process. The letters as a literary device and an integral part of the author's communicative strategy are examined not only in the context of merely grammatical parameters of temporal strata but also from the point of view of deictic and narrative use of past tense grammemes. Serbian epistolary literary discourse provides rich illustrative material for specifying the issue of deictic and narrative parameters' relevance in respect of usage of tense forms or grammemes selected for analysis. The research proves that correlation of the mentioned parameters in Serbian language context is highly interesting, however, rather complicated and controversial. The comparison of Serbian and French literary texts shows that the temporal picture of the latter is almost diametrically opposite, meaning full functionality of aorist and imperfect and limited use of analytical perfect, which is used in the reproduction of direct speech, mainly in dialogues.
Keywords: Serbian past tense grammemes, Perfect with auxiliary verb, Aorist, Imperfect, Pluperfect, chronotope of short prose forms.